Child-Friendly IRE Learning Through Digital Storytelling in the COVID-19 Pandemic - Adam Yordan; Eni Fariyatul Fahyuni (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Education is the distance of the search for knowledge to several ways to get knowledge, the COVID-19 pandemic has become an obstacle for educational institutions in conveying knowledge. With the development of digital technology, the teacher's efforts in delivering and fulfilling the rights of students by learning fun during the pandemic during the learning process are one way for students to be able and able to receive knowledge by using the child-friendly IRE learning model through digital storytelling in the SD Muhammadiyah 2 Taman environment. This article uses descriptive qualitative research in which researchers look for places of observation, with the object of research being principals, curriculum representatives, subject teachers, and distributing questionnaires using google forms and interviews to several students to find out the qualifications for fun learning. based on the results of learning research with a digital storytelling model, it becomes a fun learning solution between teachers and students when carrying out learning at home, the results of the teacher's efforts in attract students' attention when learning to use child-friendly digital storytelling with the results of research that students prefer to learn using zoom meetings in maximizing more interactive and communicative learning.